Graphene Film for Multifunctional Graphene‐Based Thermal Interface Material with Bidirectional High Thermal Conductivity - Sihua Guo; Minghe Wang; Yuanyuan Wang; Jin Chen; Kristoffer Harr; Lijie He; Yong Zhang; Yan Zhang; Bin Wei; Johan Liu (Small Structures)
Multifunctional and eco‐friendly thermal interface materials with bidirectional thermal conductivity have become outstanding materials for solving the heat dissipation problem of electronic devices. The remarkable thermal and mechanical properties of graphene establish it as a promising material for thermal management. This study introduces an environmentally friendly strategy to construct an effective thermal conductive path by assembling and stacking recycled graphene strips (GS) under external mechanical force and using them as reinforcement to strengthen epoxy resin (EP) composites. By adjusting the loading of GS, a superior vertical thermal conductivity of 104.6 W mK−1 is achieved accompanied by a parallel thermal conductivity of 10.6 W mK−1, representing enhancement of 614 and 61 times compared to that of the pure EP, respectively. The outstanding bidirectional thermal conductivity, along with ultralow thermal resistance, strong electromagnetic interference shielding, high‐efficiency Joule heating, as well as excellent mechanical properties, offers a promising way to address the thermal management challenges of next‐generation electronic devices.